The interplay between brain and behavior during development: A multisite effort to generate and share simulated datasets - Sadeghi, Neda; van der Velpen, Isabelle F.; Baker, Bradley T.; Batta, Ishaan; Cahill, Kyle J.; Genon, Sarah; McCormick, Ethan; Michel, Léa C.; Moraczewski, Dustin; Seraji, Masoud; Shaw, Philip; Silva, Rogers F.; et al. (Scientific data, 2025)
One of the challenges in the field of neuroimaging is that we often lack knowledge about the underlying truth and whether our methods can detect developmental changes. To address this gap, five research groups around the globe created simulated datasets embedded with their assumptions of the interplay between brain development, cognition, and behavior. Each group independently created the datasets, unaware of the approaches and assumptions made by the other groups. Each group simulated three datasets with the same variables, each with 10,000 participants over 7 longitudinal waves, ranging from 7 to 20 years-of-age. The independently created datasets include demographic data, brain derived variables along with behavior and cognition variables. These datasets and code that were used to generate the datasets can be downloaded and used by the research community to apply different longitudinal models to determine the underlying patterns and assumptions where the ground truth is known.